Pricing of cap-interest rates based on renewal processes - Jan Beran; Dirk Ocker (University of Konstanz, Center of Finance and Econometrics (CoFE), 2002)
Pricing of cap insurance contracts is considered for political mortgage rates. A simple stochastic process for mortgage rates is proposed. The process is based on renewal processes for modelling the length of periods with downward and upward trend respectively. Prices are calculated by simulation of conditional future sample paths. Future conditional quantiles can be obtained to assess the risk of a contract. The method is illustrated by applying it to observed quarterly mortgage rates of the Swiss Union of Raiffeisenbanks for the years 1970 to 2001.
urn:nbn:de:bsz:352-opus-8265
Keywords: 330; cap; cap rate; cap insurance; interest rate; mortgage; premium; renewal process; Poisson process; prediction; Pfandbrief; Zinsrisiko; Börsenkurs; Finanzanalyse; Schätzung; Theorie; Schweiz; Maximum-Likelihood-Methode